Planform evolution of two anabranching structures in the Upper Peruvian Amazon River. Issue 4 (26th April 2015) - Frias, C. E.; Abad, J. D.; Mendoza, A.; Paredes, J.; Ortals, C.; Montoro, H.
Abstract We present a study to relate the sinuosity of the main channel and its effect on the dynamics of the secondary channels of anabranching structures. For this purpose, two locations of the Peruvian Amazon River were selected: (1) a site with a medium to high‐sinuosity main channel (MS site: Muyuy, Peru) and (2) a site with a low‐sinuosity main channel (LS site: at the triple boundary between Brazil, Colombia, and Peru). The main channels for both the MS and LS anabranching structures have freedom to migrate in the lateral direction, while at least one of their secondary channels is adjacent to the geological valley. For MS and LS sites, temporal analysis of planform evolution was carried out using 30 years of satellite imagery from which metrics such as width, sinuosity, and annual maximum migration rates of main and secondary channels were calculated. Additionally, detailed hydrodynamic and bed morphology field measurements were carried out, and a two‐dimensional shallow water numerical model was developed. For a medium to high‐sinuosity main channel anabranching structure, the secondary channels present a dominant mechanism for reworking the floodplain, while for the low‐sinuosity anabranching structure, the main channel planform dynamics is dominant. Flow velocities along the main and secondary channels for low, transition, and high‐flow discharges describe that for MS (LS) site, the velocities are much higher along the secondary (main) channels.